Hoplitis (Hoplitis) galichicae spec. nov., a new osmiine bee species from Macedonia with key to the European representatives of the Hoplitis adunca species group (Megachilidae, Osmiini) - Müller, Andreas (Zootaxa, 2016)
Hoplitis (Hoplitis) galichicae spec. nov., a new European osmiine bee species belonging to the Hoplitis adunca species group (Osmiini) is described and diagnosed. It is currently known only from the Galichica mountain range in southwestern Macedonia. Analysis of pollen contained in the metasomal scopae revealed that all females of the type series collected pollen on the flowers of Sedum (Crassulaceae), which is unexpected as most other members of the Hoplitis adunca species group are oligolectic or mesolectic on flowers of Boraginaceae and/or Fabaceae. An identification key including all European representatives of the Hoplitis adunca species group is given.